Proporsi Komisaris Independen, Diversitas Komisaris Independen, dan Nilai Perusahaan - Rahmat Setiawan; Aulia Damanti Halim; Oriza Herlina Amalia (STIE AMKOP, 2023)
The purpose of this research is to examine the influence of proportion, age diversity, and academic major diversity of independent outside directors to firm valuation in manufacturing firms listed on the Indonesia Stock Exchange. This research uses multiple linear regression model. Data is obtained from companies financial report and companies annual report published period 2012-2016. The independent variable used in this research is proportion of independent outside directors proxied with number of independent outside directors to total board of commissioner. Age diversity of independent outside directors and academic major diversity of independent outside directors are also independent variables that proxied with 1 minus Hirschmann-Herfindahl Index. The dependent variable in this research is firm valuation measured by Tobin’s q (TBQ). The results of this research show that proportion of independent outside directors has significant positive effect to firm valuation, age diversity of independent outside directors has significant positive effect to firm valuation, and academic major diversity of independent outside directors has significant positive effect to firm valuation. Keywords: Proportion of Independent Outside Directors, Diversity of Independent Outside Directors, Firm Valuation